DETERMINANTS OF CASH HOLDINGS MODERATED BY FIRM SIZE - Wirianata, Henny; Viriany, Viriany (International Journal of Application on Economics and Business, 2023)
The study was conducted on manufacturing companies registered in IDX in 2017-2019 with purposive sampling method. Data is processed and analyzed with Eviews 10. The analytical models used are multiple regression analysis and moderation regression analysis. Data and analysis results show profitability and firm size have no significant effect on determining the amount of cash holdings. Meanwhile, liquidity and net working capital have a significant effect. The results of moderation tests show that firm size is able to moderate the influence of profitability and liquidity on the determination of the amount of cash holdings. Meanwhile, firm size cannot moderate the influence between net working capital and the determination of the amount of cash holdings in.